Supply Chain Of Fresh Fruit Bunches From Independent Oil Palm Farmers - Sarkum, Sumitro; Harahap, Arman (CV. Inara, 2025)
The purpose of this research is to determine the supply chain losses caused by fluctuations in the selling price of Fresh Fruit Bunches (FFB). The method used is to conduct direct surveys with palm oil Fresh Fruit Bunch (FFB) traders and end consumers at Palm Oil Mills in nine sub-districts in Labuhanbatu Regency. The planned number of samples to be interviewed is 800 respondents, consisting of 784 Collecting Traders and 16 SMEs, with a total of 256 respondents successfully interviewed. The research results explain the factors influencing the fluctuation of TBS purchase prices at the supplier level, namely the lack of transparency in TBS selling prices from Palm Oil Mills to traders and from traders to farmers. The findings also suggest that the local government should establish a special institution that can provide information on palm oil prices released by the government through the North Sumatra industry office. In addition, we recommend that the North Sumatra government involve district governments and other stakeholders in the context of the triple helix in sustainable development, considering the imbalanced needs and productivity in implementing national strategic programs. The next research question is about the sustainability of small-scale oil palm farmers, considering the continuous growth of oil palm. Policymakers in key stakeholder institutions need to design strategies to manage global disruptions in palm oil trade, particularly by involving farmers in national strategic programs, one of which focuses on concentrating development on palm oil downstreaming.